A Novel Step-Up Power Converter Configuration for Solar Energy Application - Ghaderi, Davood; Bayrak, Gokay (Elektronika ir Elektrotechnika, 2019)
Renewable Energy Sources (RES) including full cells, wind turbines, and photovoltaic panels, widely are spreading. Among all the renewable energy sources, solar power generation system tops the list. The first choice is the boost converter when the voltage step-up is the issue. But the most important subject is applying an efficient structure with high gain, cheap and quick controller circuit. Our proposed cascaded boost converter is one of such converters which consists of several cheap components such as diode, inductor, capacitor and power switch, which has same switching frequency and phase shift in comparison with conventional boost converters. In comparison with the classic cascaded boost converter, the voltage gain for the proposed structure is very high and by forming a preamplifier layer, for a duty cycle of 80 % by adding only two diodes, one inductor, and one capacitor for the second block, voltage gain is increased by 5 times compared to the classic boost converter. The proposed method provides the increased output voltage along with the duty cycle. The projected strategy has been verified with the help of Matlab/Simulink. Also, a hardware implementation of the proposed converter has been done around 200 W by applying a Jiangyin HR-200W-24V type solar panel.